(untitled) (Research, Society and Development, 2021)
The consumption of medicinal plants has shown considerable growth in several countries. Annona sylvatica, commonly known as araticum-do-mato, is a fruit used in folk medicine to lower blood pressure. The objective of this work was to investigate the phytochemical profile and evaluate the antioxidant activity of A. sylvatica leaf extracts and fractions. The ethanol extract was obtained by maceration and submitted to liquid-liquid partition to obtain fractions in hexane, chloroform and ethyl acetate. The main classes of secondary metabolites were detected by phytochemical screening, the content of total phenols (TF) and the antioxidant activity were quantified by the Folin-Dennis tests and the DPPH radical scavenging activity assay, respectively. Using the Pearson coefficient, the total phenol contents were correlated with the EC50 values observed in the DPPH assay. Phytochemical screening detected the presence of flavonoids, saponins, alkaloids and triterpenes/steroids. The AcOET fraction showed the highest content of total phenols and the highest activity in the DPPH assay, with values of 84.0±4.4 mg GAE. g-1 and EC50 9.28 µg. mL-1, respectively. There was a strong negative correlation between TF content and EC50 values, suggesting that part of the antioxidant activity observed is related to TF content. The results suggest that araticum-do-mato is an important source of natural antioxidants.